SEXUAL VIOLENCE AGAINST CHILDREN: Prevention Efforts in Jambi - Harahap, Anggi Purnama; Adawiyah, Robi'atul; Sasnifa, Pidayan; Mukhlisa, Dian (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
This study aims to carefully investigate sexual violence against children and its countermeasures in Jambi City. The increasingly massive increase in violence against children has become a concern in recent years. This research is empirical legal research employing observation, interviews, and document analysis to collect qualitative data. The research findings show that the problem of sexual violence against children in Jambi City is still a serious issue that requires attention and optimal action steps. Factors such as lack of public understanding, lack of supervision, and low legal awareness are the main contributors to the high rate of sexual violence against children. In addition, this study also assessed the efforts that the government, non-governmental organizations, and the community have made in tackling sexual violence against children. It found a lack of interagency coordination and a need to improve community outreach and education on the issue. Based on these findings, the study recommends policy improvements and increased cooperation between government and non-government agencies in addressing child sexual abuse. Strengthening community outreach and education is also needed to raise awareness and prevention at the community level. Overall, cross-sectoral cooperation from various parties is a must to create a safe environment and protect children from sexual violence in Jambi City.